Long non-coding RNA PRR7-AS1 promotes osteosarcoma progression via binding RNF2 to transcriptionally suppress MTUS1 - Chen-Xi, Gu; Jin-Fu, Xu; An-Quan, Huang; Xiao, Yu; Ying-Hui, Wu; Suo-Yuan, Li; Cong, Shen; Tian-Ming, Zou; Jun, Shen (Frontiers in Oncology, 2023)
Introduction Osteosarcoma is a common bone malignant tumor in adolescents with high mortality and poor prognosis. At present, the progress of osteosarcoma and effective treatment strategies are not clear. This study provides a new potential target for the progression and treatment of osteosarcoma. Methods The relationship between lncRNA PRR7-AS1 and osteosarcoma was analyzed using the osteosarcoma databases and clinical sample testing. Cell function assays and tumor lung metastasis were employed to study the effects of PRR7-AS1 on tumorigenesis in vivo and in vitro. Potential downstream RNF2 of PRR7-AS1 was identified and explored using RNA pulldown and RIP. The GTRD and KnockTF database were used to predict the downstream target gene, MTUS1, and ChIP-qPCR experiments were used to verify the working mechanismy. Rescue experiments were utilized to confirm the role of MTUS1 in the pathway. Results Deep mining of osteosarcoma databases combined with clinical sample testing revealed a positive correlation between lncRNA PRR7-AS1 and osteosarcoma progression. Knockdown of PRR7-AS1 inhibited osteosarcoma cell proliferation and metastasis in vitro and in vivo. Mechanistically, RNA pulldown and RIP revealed that PRR7-AS1 may bind RNF2 to play a cancer-promoting role. ChIP-qPCR experiments were utilized to validate the working mechanism of the downstream target gene MTUS1. RNF2 inhibited the transcription of MTUS1 through histone H2A lysine 119 monoubiquitin. Rescue experiments confirmed MTUS1 as a downstream direct target of PRR7-AS1 and RNF2. Discussion We identified lncRNA PRR7-AS1 as an important oncogene in osteosarcoma progression, indicating that it may be a potential target for diagnosis and prognosis of osteosarcoma.